Compostable wood composites

A biodegradable composite with a swelling wood particle layer and polymer matrix addresses the limitations of PLA by ensuring rapid compostability and structural integrity in thick-walled containers, meeting EN13432 standards.

JP7607336B2Active Publication Date: 2024-12-27SULAPAC OY
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
JP2021510716
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-01
Filing Date
2019-09-02
Publication Date
2024-12-27
Estimated Expiration
2039-09-02

AI Technical Summary

Technical Problem

Existing biodegradable polymers like PLA face limitations in thickness due to slow degradation rates and inability to maintain structural integrity when exposed to liquids, making them unsuitable for thick-walled containers that require long-term stability and compostability according to EN13432 standards.

Method used

A biodegradable composite material comprising a biodegradable polymer matrix with hydrophilic wood particles that swell upon water absorption, combined with a second layer lacking such particles, is used to form a multilayer structure through injection molding, ensuring rapid degradation and mechanical stability.

Benefits of technology

The composite achieves rapid compostability within 6 months, maintaining structural integrity for up to 12 months in wet conditions, meeting EN13432 standards and suitable for thick-walled containers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607336000004
    Figure 0007607336000004
  • Figure 0007607336000005
    Figure 0007607336000005
  • Figure 0007607336000006
    Figure 0007607336000006
Patent Text Reader

Abstract

A cosmetic container and method for manufacturing the same. The container, such as a bottle, has a wall formed by a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix in combination with particles of a hydrophilic material mixed therein that can swell within the matrix upon absorption of water. The container further comprises a second layer of compostable material comprising a biodegradable polymer forming a continuous matrix and that is substantially free of particles of the hydrophilic material that can swell within the matrix, or contains substantially fewer particles than the first layer. The container is degradable in compost, with disintegration of the container wall occurring within 12 weeks at 58°C. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] BACKGROUND OF THEINVENTION (Technical field) The present invention relates to the manufacture of three-dimensionally formed compostable composite articles by melt processing. In particular, the present invention relates to the use in such a method, in particular by an injection molding process, of a composition comprising a continuous matrix of a thermoplastic biodegradable polymer and wood particles distributed within the matrix. The present invention also relates to compostable articles such as containers and other packaging articles. [Background technology]

[0002] Description of the Prior Art Currently, the annual production of plastics is about 320 million tons, with about 40% of the plastic produced being used in the packaging sector. The production of packaging plastics is expected to reach 1.2 billion tons per year by 2050. Plastics are commonly used in food storage due to their low cost, light weight and hygienic production. Recent studies have shown that more than 50% of plastic waste is sent to landfills, which amounts to about 60-100 million tons per year. EU member states generated about 25 million tons of used plastics in 2014, of which only 30% was recycled. Moreover, it is estimated that in 2010, 5-13 million tons of plastic waste was discharged into the environment, especially the oceans (European Commission: Strategy on plastics in a Circular Economy, 2016).

[0003] Various mass production industries, such as the food packaging sector, are attempting to reduce their dependency on mineral oil-based raw materials due to the shortage of non-renewable mineral oil. The main focus has shifted to biopolymers, as they are considered to be an ecological alternative to traditional materials based on fossil resources. The industry is also focusing more on biodegradable materials due to the ambivalence regarding non-degradable materials. When oily, non-biodegradable disposable plastic products are discarded in the environment, they are subjected to a slow degradation into microplastics. This process continues for years and even decades. As a result, a large amount of discarded packaging is excluded from recycling. Given the environmental issues associated with plastics, plastic waste management is a key issue that needs to be seriously considered. Therefore, there is a need to develop biodegradable materials that can be composted and biodegraded in an environmentally friendly manner within a relatively short period of time. In this framework, bio-based polymers play a key role, as they help to reduce the emission of toxic greenhouse gases (GHGs), such as carbon dioxide (CO2).

[0004] Examples of biodegradable polymers used in packaging include starch, cellulose, chitosan, polylactic acid (PLA), polycaprolactone (PCL), polyhydroxybutyrate (PHB), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS) and their blends. Some materials can be mixtures or blends that contain synthetic components such as other polymers and additives to improve the functional properties of the final products and expand the range of their applications. According to a recent market data report on bioplastics, PLA production is the largest sector by type with a market share of about 40%.

[0005] PLA is an example of a biodegradable synthetic thermoplastic polyester derived from renewable resources such as sugars from sugarcane or corn and other plants, and is one of the most commonly used bioplastics today. PLA is also very durable and stiff, with excellent processing properties for most applications. PLA does not degrade rapidly in low temperature and humidity, but it does degrade rapidly when exposed to high humidity and high temperatures (above 60°C). Biodegradation of PLA is a two-step process consisting of hydrolysis to low molecular weight oligomers followed by complete digestion by microorganisms. Applications of PLA range from the food sector to biomedicine, but are limited by the high price of the polymer and its slow rate of degradation in nature.

[0006] To meet the requirements of the European composting standard according to EN13432, commercially available products made from biodegradable polymers and natural fillers are often limited to thin-walled applications such as films and food utensils and containers. Most of them are manufactured from the following types of materials and have wall thicknesses suitable for composting: PLA-based Bio-Flex® up to 140 μm, Ecovio® up to 1.1 mm, CorbionPLA up to 1.0 mm, PHA-based Mirel® up to 0.7 mm, Mater-bi® based on starch and vinyl alcohol copolymer up to 1.0 mm, Inzea® based on starch and PLA up to 1.5 mm, and polycaprolactone CAPA® series up to 1.0 mm (Tu:v Austria, OK compost certified Products; 2016, hereafter referred to as “OK Compost”). Rigid packages made of the PLA blend EcovioT® (BASF) have a maximum thickness of 1.2 mm.

[0007] In a previous study, PLA deli containers were completely degraded in 30 days. However, in the case of PLA bottles, some PLA residues were found even after 30 days of composting, until the maximum temperature rose above 60°C (Kale et al., 2007). It has been shown that the biodegradation time of PLA products is highly dependent on the wall thickness of the article.

[0008] Due to the thickness limitations mentioned above, the above types of OK Compost Approved materials cannot be used, for example, for the storage of liquid foods that require a shelf life of 90 days or cosmetics that require a shelf life of at least 12 months. Although these materials can successfully maintain their properties in a dry state for a relatively long period of time before use, if placed in direct contact with liquids, they will leak and begin to degrade within a month.

[0009] In recent years, the development of biodegradable and compostable materials has focused on renewable resources, such as bio-based and biodegradable polymers, natural fibers derived from forest industry residues, and by-products from the coffee, cosmetics, and grain-based ethanol industries, etc. In addition, agriculturally derived fibers (such as wheat straw) and lignin-containing materials such as hemp stalks may be utilized as fillers.

[0010] US 8,722,773 relates to a polymer composite material containing 65-90% by weight of chemical wood pulp fibers from a chemical wood pulp sheet uniformly dispersed within a thermoplastic polymer matrix. The polymer and chemical wood pulp were mixed and processed in a melt process. US 8,722,773 discloses a material that uses kraft bleached chemical wood pulp to avoid the discoloration and odor problems associated with natural fibers such as kenaf and wood fibers, due to lignin and other compounds present in such materials. However, for the manufacture of composite materials, natural fibers are less expensive and therefore more attractive than the highly refined and bleached fibers described in, for example, US 8,722,773.

[0011] A composite material containing wood particles is disclosed in JP 2002-113822. This publication suggests a layer structure having a base layer with a thickness of 1-30 mm and containing less than 50% by weight of wood particles with a diameter of 1-30 mm, and a surface layer covering the base layer and containing wood particles with a diameter of up to 50-300 μm. The thickness of the surface layer is selected to be sufficient to cover the base layer. No specific application of the material is suggested in the document. In addition, the two-layer structure described in JP 2002-113822 requires the use of wood particles from at least two different particle sources, two different polymer blends and a manufacturing process based on coextrusion.

[0012] The above documents disclose polymeric materials based on the processing of fossil-based raw materials such as polystyrene, polyacrylates, polyesters, polyamides, poly(etherimides) and acrylonitrile butadiene styrene type copolymers.

[0013] The composition of the compostable polymer, PLA and finely ground cellulose material, is disclosed in International Publication No. WO2015 / 048589. This document describes an annealed PLA composite containing PLA and up to 30% finely ground cellulose material (such as finely ground paper from paper pulp). The finely ground particles have a size of 10-250 μm, specifically 20-50 μm, with a narrow particle size distribution. According to the publication, the material is compostable and exhibits a high deflection temperature under load (HDT). However, the addition of the finely ground material does not appear to provide any mechanical advantage, and the maximum loading of the material was limited to 30% to avoid problems during processing and injection molding.

[0014] Further composite materials are described in Chinese Patent Publication No. 101712804 (CN101712804A), US Patent Publication No. 2013253112 (US2013253112), US Patent Publication No. 2016076014 (US 2016076014), US Patent Publication No. 2002130439 (US 2002130439) and European Patent Publication No. 0319589 (EP0319589).

[0015] Wood-based composites are widely used in a variety of applications because they are environmentally friendly, lightweight and relatively low-cost materials. There are numerous examples of wood composites, and they are usually created by using some kind of binder to bond strands, fibers, or wood boards. Such types of products are also known as engineered wood, manufactured boards, or laminated timber. The term wood plastic composite (WPC) is used for materials that contain wood fibers and thermoplastics such as polyethylene (PE). Similar types of composites can also be produced from plant fibers. The use of additives in these materials is also common. This is because they allow the binding of biopolymers with natural fibers, which provides benefits in processing. One of the most advantageous features of WPC is that wood waste can be used in the formulation, which reduces the need to destroy virgin forests.

[0016] Plywood is considered the first wood composite product. Plywood is made from sheets of cross-laminated veneer plies, which are finally bonded with moisture-resistant adhesives under heat. Another example of a wood composite is fiberboard, which is made by combining wood fibers with wax and resin binders under high temperature and pressure. Particleboard is made from wood chips or lumber saw shavings pressed with synthetic resins (US Patent Application Publication No. 2018215972).

[0017] Wood used in WPC is milled, screened and dried before extrusion. For decking and fence profiles, when a rough surface texture is acceptable or desired, screening the wood fibers to 40-60 mesh provides good flow properties and facilitates mixing into the polymer matrix. For profiles that require a smooth finish, the wood is sieved through an 80-100 mesh screen. Fines that pass through a 120 mesh screen are undesirable because they have poor flow properties and are unevenly distributed in the polymer matrix during extrusion. Unevenly distributed wood fibers, so-called "wood spots", are a common quality problem, especially when the wood contains excessive fines or when the extruder is too worn to obtain a uniform mixture (CN 107932874).

[0018] WPC already has a strong reputation for extrusion into deck boards, fence boards, etc. Currently, development is moving towards injection molding (IM), which is a more demanding manufacturing technique than extrusion.

[0019] Many challenges are faced during IM of WPC, including unreliable quality and supply, and generally, WPC is very difficult to process when compared to more familiar IM materials such as PE. The most commonly used raw material type for IM is pellets or granules containing a mixture of wood and polymer. The pellets or granules are fed into the hopper of the IM device. The problem associated with feeding the pellets is the size of the pellets and the moisture content of the material. If the pellets are physically too large, they tend to melt unevenly and create additional friction, resulting in a structurally inferior final product (JP 2010-280152 A, US 2006 / 0267238 A, US 6210792 B, US 6632863 B). Drying of the material is also an important quality parameter. Moisture level in WPC increases with the amount of wood filler in the composite. Low moisture content is required for best results in both extrusion and IM, although the recommended moisture level for IM is slightly lower (Canadian Patent Application Publication No. 1171656).

[0020] IM of WPCs also faces many chemical challenges. The first problem associated with WPCs is the need to create strong chemical bonds between the hydrophilic wood fibers and the hydrophobic polymer matrix. The volume of the wood filler depends on the moisture, while the volume of the plastic matrix depends on the temperature. This can lead to internal shear stresses that can cause cracks in the final product. Cracking not only deteriorates the mechanical properties of the material, but also increases the surface area of ​​the wood fibers exposed to moisture, increasing the risk of accelerated decay and decay. To overcome these problems, coupling agents are used. The purpose of the coupling agent is to improve the adhesion between the wood filler and the matrix. Coupling agents also reduce the hydrophilicity of the wood filler. The hydrophilicity of the wood filler can also be affected by various treatments of the wood filler before compounding. This is very important, as WPCs made using untreated wood lack long-term durability.

[0021] When manufacturing injection moulded products, it is very important to use the right type of wood filler. It is preferable to use wood derived from recycled wood or sawdust. Other residues from the forest industry can also be used. This is due to the reduced LCA value and lower costs. This type of wood needs to be mechanically and chemically treated (WO 2015 / 049589). During mechanical treatment, the wood fibres are cut to the desired size and shape. When chemically treated, the wood is chemically modified, reducing moisture absorption and strengthening the bond between the wood fibres and the polymer matrix. In other words, to ensure optimal performance of WPC, the wood needs to be treated. Regardless of the treatment applied to the wood, it needs to be dried, as moisture weakens the bond between the wood fibres and the polymer, increasing the risk of fungal attack and causing the material to rot.

[0022] Based on the above facts, there remains a need for biodegradable materials that can be formed into containers while maintaining stability to selected chemicals for extended periods of time. At the same time, they should be able to pass composting tests according to the EN13432 (or harmonized EN13432:2000) compost standard. Such products should also comply with the requirements of the EU Packaging Directive (94 / 62 / EEC). Summary of the Invention

[0023] The object of the present invention is to eliminate at least some of the disadvantages of the prior art and to provide a new material which can be cost-effectively produced using injection moulding and which is degradable under industrial composting conditions even for products with walls thicker than 1 mm, in particular thicker than 1.2 mm, up to 25 mm or even more.

[0024] In developing thick materials that are degradable in a composting environment, it is important that water penetrates the structure and starts to break down the polymer chains, forming small polymer fractions that eventually biodegrade into CO2, water, inorganic compounds and biomass, leaving no microplastics, visible pollutants, or toxic residues. Traditionally, this is only possible with thin, sheet-type materials with a thickness of less than 1 mm.

[0025] The present invention is based on the idea of ​​combining hydrophilic material particles, such as coarse wood particles, with a biodegradable polyester matrix to form a first composition. It has been shown that the swelling of hydrophilic particles, such as wood particles, such as chips, having a screen size of more than about 0.5 mm, such as more than about 1 mm, and less than about 25 mm, such as less than 10 mm, such as up to 2.5 mm or 2 mm, accelerates the cracking and fragmentation of the polymer matrix.

[0026] In addition to the first composition, at least one second composition is also used, which contains significantly less or no hydrophilic particles.

[0027] Thus, the present invention provides a container having a wall formed by a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix in combination with particles of a hydrophilic material mixed therein that can swell within the matrix upon absorption of water, and by at least one second layer of compostable material comprising a biodegradable polymer forming a continuous matrix and containing less or substantially no such particles of hydrophilic material that can swell within the matrix upon absorption of water.

[0028] forming a first mixture comprising a biodegradable polymer having mixed therein particles of a hydrophilic material capable of forming a continuous matrix and swelling within the matrix upon absorption of water; forming a second mixture comprising a biodegradable polymer that forms a continuous matrix and contains fewer particles of a hydrophilic material that is capable of swelling within the matrix upon absorption of water; processing the first and second mixtures by injection molding to form a container wall comprising layers of the first and second mixtures in an overlapping arrangement; A method for manufacturing such a container, comprising:

[0029] The material will achieve excellent compostability properties in combination with good mechanical properties, especially when used in the form of a multi-wall. The water absorption rate of a 45 ml bottle with a wall structure containing or comprising the above-mentioned thermoplastic biodegradable material is 0.061 mg / (day cm) within 33 days by NTP. 2 )Super 2.0mg / (day·cm 2 ) or less.

[0030] More specifically, the invention is characterized mainly by what is stated in the characterizing parts of the independent claims.

[0031] The present invention provides considerable advantages. An embodiment of the material meets OK Compost Approval. Thus, in accordance with achieving OK Compost Approval for a material, the material meets the following specifications (requirements): In compost, complete biodegradation of the material at 58°C occurs within a maximum of 6 months; Biodegradation reaches a level of 90% of the product mass; Disintegration of the product at 58°C occurs within 12 weeks; Due to the level of disintegration exceeding 90%, at most only 10% of the residue does not pass through a 2 mm sieve.

[0032] At the same time, the use of the present natural fiber particles, especially coarse wood particles such as wood chips, makes it possible to generate mechanical, physical and chemical properties that are good enough for the material to be used in the manufacture of thick-walled packages, such as bottles for cosmetic packaging. Small particles such as sawdust and other powders and fibrils cannot effectively increase the compostability due to water absorption and swelling. Moreover, large particles interfere with the manufacturing process and decompose too quickly, preventing the proper use of the material for thick-walled packages.

[0033] In wet conditions, moisture absorption of wood components combined with temperature-induced movement of the polymer matrix causes deformation in WPC. The moisture-related volume change increases with the size of hydrophilic particles such as wood particles. This increases deformation and increases internal tensions in WPCs with flakes or fibers of wood material, usually with screen sizes greater than 0.5 mm, especially 1 mm or larger. The tensions created in WPCs cause microcracks to form, exposing the wood filler to oxygen and moisture and increasing the overall surface area. This causes fungal attack and loss of tensile strength.

[0034] Wood fillers exposed to water for extended periods of time will lose tensile strength. Thus, the loss of tensile strength is not only the result of cracking, but also the increase in exposed filler and the loss of tensile strength of the exposed filler. Chips or fibers tend to break down into smaller fractions during compounding, thus changing their size and shape.

[0035] The second composition, preferably free of hydrophilic particles, can form a surface layer on one or both sides of the layer formed from the first composition. Such a surface layer is usually thin (reaching a maximum thickness of 1 mm) and delays the onset of water-induced degradation of the layer formed from the first composition. When aqueous materials are contained in the container, an inner surface formed by a biodegradable polymer free of or substantially free of hydrophilic particles improves the water resistance of the container wall, for example, for up to 6 or 12 months. When water begins to penetrate through the inner or outer coating into the layer formed from the first composition, degradation begins rapidly, as shown above and in the following examples.

[0036] The present invention will now be examined in more detail with reference to the detailed description and accompanying drawings. [Brief description of the drawings]

[0037] [Figure 1] 1 is a graph showing the water absorption of wood / PLA composites containing various additives at 50° C. [Diagram 2] Figures 2a to 2c are photographs of the three sample bottles before the industrial composting test. [Diagram 3] 3a-c are photographs depicting the decomposition of sample Com-2 in industrial compost. [Figure 4] 1 shows a cross section of the bottle used in the water absorption test. [Diagram 5] 1 is a bar graph showing the water absorption of the test bottles in weight percent at 22° C. where the tests were conducted. [Figure 6] 1 is a bar graph showing water intake as a percentage of bottle weight over a one week period. [Figure 7] Microscopic images of Sula 40 wood composite sample. Figure 7a shows the surface after contact with Oil Red O stained water for 94 days at 23 °C. Figure 7b shows the cross section after contact with Oil Red O stained water for 94 days at 23 °C. [Figure 8] 1 is a bar graph showing the roughness of the inner and outer walls of containers produced by injection molding using composite materials with different wood particle contents. [Figure 9A] 1 is a SEM micrograph showing a pure PLA surface. [Figure 9B] 1 is a SEM micrograph showing a PLA-wood composite containing 10% wood by weight. [Figure 9C] 1 is a SEM micrograph showing a PLA-wood composite containing 30% wood by weight. [Figure 9D] 1 is a SEM micrograph of a PLA-wood composite containing 40% wood by weight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] In the present context, the term "thick-walled" container refers to a container having walls with an average thickness of more than about 1 mm, in particular the walls are typically between 1 mm and 25 mm.

[0039] "WPC" stands for wood-polymer-composites.

[0040] In this context, the provided compositions and corresponding layers having different contents of hydrophilic particles that can swell upon contact with water are referred to in the singular as the "first" composition and "first" layer, and the "second" composition and "second" layer, respectively. However, it should be understood that the present technology also provides several first compositions and several second compositions and corresponding layers in the same product. Usually, there are 1-3 first layers and 1-5 second layers.

[0041] In one embodiment, there is one first layer and one second layer, in another embodiment, there is one first layer and two second layers.

[0042] In the present context, "hydrophilic materials" capable of swelling in a matrix upon absorption of water usually refer to non-fibrillated (i.e. mechanically disintegrated) natural materials that swell upon absorption of water. The swelling is usually so intense that pathways are formed in the polymer matrix that allow the penetration of water, in particular at least partially liquid water. This function has already been explained above. Natural materials are usually represented by trees, plants, other plant materials, and cereals and their parts.

[0043] In one embodiment, the hydrophilic material comprises, consists of, or consists essentially of particles of wood or lignocellulosic material or cellulose or hemicellulose or combinations thereof. In one embodiment, the present technology provides a material, in particular a compostable wood composite material. Such a material can be provided in the form of a layered material comprising a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix and having mixed therein particles of hydrophilic material capable of swelling within the matrix upon water absorption, and a second layer of compostable material comprising a biodegradable polymer forming a continuous matrix and free or substantially free of particles of hydrophilic material capable of swelling within the matrix. In one embodiment, the second layer comprises a biodegradable polymer having substantially fewer particles of hydrophilic material capable of swelling within the matrix than the first layer.

[0044] The material may be used, for example, in containers.

[0045] In one embodiment, a container for cosmetics and similar water-based or oil-based products has a wall formed by at least one first layer and at least one second layer. The first layer usually comprises a biodegradable polymer forming a continuous matrix in combination with particles of hydrophilic material that can swell within the matrix upon absorption of water mixed therein. The second layer comprises a compostable material comprising a biodegradable polymer forming a continuous matrix and substantially free of particles of hydrophilic material that can swell within the matrix or containing substantially fewer particles than the first layer. The second layer provides a barrier against migration of water-based or oil-based products stored in the bottle to the first layer for a predetermined period of time, usually at least 3 months, in particular 6 to 12 months, at ambient temperature, for example about 15 to 25 ° C.

[0046] The particles of hydrophilic material capable of swelling within the matrix on absorption of water are preferably chosen from particles obtained by mechanical treatment of wood or other lignocellulosic materials, such as annual or perennial plants and plant residues.

[0047] In one embodiment, the particles of hydrophilic material comprise wood particles, in particular "coarse" wood particles. Such particles typically have a screen size of more than 0.5 mm, in particular 1 mm or more, and 25 mm or less, in particular 10 mm or less, 2.5 mm or less, or 2 mm or less.

[0048] The term "screened" size is used to designate particles that have been sized or separated using a screen having a mesh size that corresponds to the sorting size of the particle, or particles that can be sized or separated to a particular size.

[0049] The container is thick-walled, i.e., it has a total wall thickness of 1 mm to 25 mm, usually about 1.2 to 10 mm.

[0050] Typically, the thickness of the first layer (or the total thickness of the first layers) is greater than the thickness of the second layer or the total thickness of several second layers. In particular, the ratio between the thickness of the first layer and the thickness of the second layer (or the combination of second layers) is about 1.1:1 to 100:1, for example 1.2:1 to 10:1.

[0051] In one embodiment the second layer has a thickness of up to 1 mm, while the first layer has a thickness of up to 20 mm, typically up to 10 mm.

[0052] In one embodiment of the present technology, the first composition comprises a matrix of a thermoplastic polymer having a melting point above 110°C and having hydrophilic particles of a hydrophilic material distributed in the thermoplastic polymer matrix and capable of swelling within the matrix upon absorption of water.

[0053] The particles of hydrophilic material are preferably formed by non-fibrillated wood particles having a sieving size of at least 0.5 mm, or at least 1 mm, preferably at most 25 mm, preferably at most 10 mm, for example at most 2.5 mm or 2 mm. At least a part of the wood particles is present in the form of wood chips. In particular, at least 20% by volume, for example 30-90% by volume, of the wood particles is present in the form of wood chips, such chips usually being "flat-shaped", as discussed below.

[0054] The weight ratio of thermoplastic polymer to wood particles is typically in the range of 35:65 to 90:10, for example 50:50 to 85:15, 55:45 to 80:20, or 60:50 to 80:20.

[0055] In a preferred embodiment, the composite material comprises 5-60% by weight, in particular 10-55% by weight, for example 20-50% by weight, or 15-45% by weight, or 15-40% by weight, of wood particles, calculated on the total weight of thermoplastic polymer and wood particles and other solid components.

[0056] In one embodiment the wood particles comprise particles having a sieve size of less than 20 mm.Thus, in one embodiment at least 70% by weight of the wood particles, preferably at least 80% by weight, typically 80-95% by weight, have a sieve size in the range 0.5-10 mm, in particular 1-2.5 mm, or 1-2 mm.

[0057] The wood particles of the composition are at least partially formed by particles having a non-cubic shape. Such particles can be characterized as chips, and such particles are usually "plate-like" or "flat", "slate-like" or "flat-shaped". In one embodiment of the present invention, the wood particles of the composition are particles obtained by chipping of a wood raw material. In the present context, wood particles are considered to be wood chips if they have a general planar structure, with a planar cross-sectional thickness that is usually less than 40%, in particular less than 25%, for example less than 10%, of the maximum planar dimension of the particle. Shaving wood inevitably results in a finely divided particulate material that contains wood chips and wood shavings, together with particles with various other shapes. Thus, the composition may also contain sawdust and wood flour (less than 1 mm in size). However, usually, the majority of the volume of the wood particles are generally chips (i.e., they have a "plate-like" or "slate-like" general shape of "flat" or "flat-shaped" particles).

[0058] As discussed above, such particles, e.g., wood chips included in embodiments of the present technology, will contribute to good dispersion of the wood material within the polymer, and good processability of the material in polymer processing equipment. As a result, relatively large wood particles, e.g., having a typical (80%) particle size of 1.0-2.5 mm, can be used. Furthermore, it has been found that wood chips pass smoothly through the nozzle portion of melt processing equipment, such as injection molding equipment, and do not impede the melt flow rate of the composite material.

[0059] Current wood particles are usually "non-fibrillated", meaning that they are obtained by mechanical treatment. Thus, in one embodiment, the particles of hydrophilic material are obtained by crushing, chipping, shaving, grinding or refining natural materials such as wood or other lignocellulosic materials such as annual or perennial plants and plant residues.

[0060] In one embodiment, this mechanical treatment is different from the treatment in which fibers are liberated from wood by fibrillation, in particular by refining or grinding chips or logs, or by pulping wood raw materials by chemical means, such as pulping with chemical pulping liquor. Such treatment produces "fibers" or "fibrils". Nevertheless, it is possible to incorporate into the composition a portion of the fibers or fibrils, in particular fibers or fibrils derived from lignocellulosic materials, such as wood materials, in addition to non-fibrillated wood particles. Usually, such fibrillated components form less than 50% of the total weight of the non-polymeric portion of the composition. In particular, the fibrillated components form less than 40% by weight, such as less than 30% by weight, suitably less than 20% by weight, such as less than 10% by weight or even less than 5% by weight of the total weight of the non-polymeric portion of the composition.

[0061] Suitable fibers may be obtained from woody materials including lignocellulosic materials such as annual and perennial plants, or plant residues remaining after crop harvest such as grass, hay, straw, bamboo, kenaf, hemp, jute, rice, soybean, grass seeds, etc.

[0062] Also, crushed seed husks of cereals may be used, in particular oats, wheat, rye, barley and coconut husks.

[0063] The wood particles may be derived from conifers or hardwoods, including pine, spruce, larch, juniper, birch, alder, aspen, poplar, oak, maple, eucalyptus, and mixed tropical hardwoods. In a preferred embodiment, the wood material is selected from hardwoods, particularly poplar species hardwoods such as poplar or aspen, or from birch. The use of non-coniferous woods may avoid the outgassing of terpenes and other volatile components during the melting process, which is typical of coniferous species. Also, bark, which forms the outermost layer of the stems and roots of woody plants, is a suitable organic filler material. Bark-bearing plants include trees, woody vines, shrubs, etc. Cork, which is rich in suberin, may also be utilized.

[0064] The second composition comprises a matrix of a thermoplastic polymer having a melting point above 110°C, forming a continuous matrix, and being substantially free of particles of hydrophilic material capable of swelling within the matrix, or containing a substantially lower amount than the first layer. In one embodiment, the second mixture contains less than 50% by weight, in particular less than 25% by weight, for example less than 10% by weight, preferably less than 5% by weight, of particles of hydrophilic material capable of swelling within the matrix upon absorption of water. Any hydrophilic material and particles thereof of the second layer may be selected from the hydrophilic materials and particles described above in relation to the first layer.

[0065] In one embodiment, the same hydrophilic material and particles are used in the first layer and the second layer, and the difference between the first layer and the second layer is that the second layer contains less hydrophilic material.In one embodiment, the content of hydrophilic material in the second layer is less than 50% by weight, in particular less than 40% by weight, for example less than 30% by weight, usually less than 20% by weight, for example less than 10% by weight, of the content of the first layer.In one embodiment, the second layer does not contain hydrophilic natural material in particle form, i.e. it comprises, essentially consists of, or consists of neat polymer.

[0066] Both the first and second compositions preferably comprise a matrix of a biodegradable thermoplastic polymer, in particular the thermoplastic polymer having a melting point above about 150°C, in particular above about 155°C.

[0067] The surface of the molded part, for example its smoothness and appearance, depends on the amount of water contained in the material used for injection molding. Thus, water in the polymer can become a problem as the processing temperature of the polymer approaches 200°C, as water will boil out of the polymer.

[0068] Based on this, in one embodiment, the amount of moisture ("moisture content") in wood particles, eg, wood chips, is adjusted to less than 250 ppm, eg, less than 50 ppm, prior to treatment.

[0069] In one embodiment, the biodegradable polymers used are dried or have been dried before processing, for example before injection molding. In addition to biodegradable polymers, such as polyesters of the poly(hydroxy acid) type, some other polymers are also preferably dried before use. Examples include polyamides and polycarbonates. Thus, the water content of thermoplastic polymers, in particular biodegradable polymers or biopolymers, such as PLA or other polyesters based on hydroxy acids, is preferably less than 500 ppm, in particular less than 250 ppm, respectively. This embodiment is considered in more detail below.

[0070] In one embodiment, the first composition and optionally also the second composition contain a mineral filler. In a preferred embodiment, the mineral filler is formed by slate-like particles such as talc or kaolin. Another filler is formed by silica. Usually, the content of mineral filler, if any, amounts to about 0.1 to 40%, in particular about 0.5 to 30%, calculated from the total weight of thermoplastic polymer and wood particles.

[0071] The slate-like mineral pigment may provide improved barrier properties to the composition. The slate-like mineral pigment may also function as a processing aid during melt processing of the composition. Silica, a finely divided silicon dioxide material, improves melt flow properties.

[0072] Other mineral fillers and pigments may also be present in the first and second compositions.

[0073] Typically, the total content of mineral fillers, including slate-like mineral pigments, is less than 50% of the non-polymeric portion of the composition. Examples of mineral fillers and pigments include calcium carbonate, calcium sulfate, barium sulfate, zinc sulfate, titanium dioxide, aluminum oxide, and aluminosilicates. In one embodiment, the composite material further contains particles of finely divided material capable of imparting color properties to the composite material. The dyeing material may be selected, for example, from natural materials having stable colors at the processing temperatures used during melt processing. In one embodiment, the dyeing material is stable at temperatures up to 200°C.

[0074] Fatty acid metal salts may be used as processing aids and deoxidizers. The primary function of metal stearates is their ability to prevent the composite from sticking to the mold or to itself. However, for practical purposes, commercially available metal salts are limited to those derived from stearic, palmitic, lauric, oleic, and tall oil acids. Stearic acid is a straight-chain saturated-basic acid found in vegetable or animal fats. The two metal stearates applicable for injection molding are calcium and zinc. The amount of stearate used is 0.5-5% by weight.

[0075] In one embodiment, the wood component (wood granules) is chemically modified. The chemical modification can be carried out using chemical reagents, usually monomeric reagents. Among such reagents, acid anhydrides, inorganic acid esters, acid chlorides, chloroethers, aldehydes, lactones, reactive vinyl compounds, epoxides, isocyanates, and metal salts of organic acids, such as metal salts of carboxylic acids, are particularly useful compounds.

[0076] One embodiment involves the use of maleic anhydride, which has a ring anhydride group that can readily react with hydroxyl groups on the wood matrix without adversely affecting the environment, resulting in a reduction in the amount of hydroxyl groups. The amount of anhydride used is 1-5% by weight.

[0077] Oleic acid amides and waxes are used as lubricants in injection molding and to reduce internal friction. They can also protect wood fibers from water absorption. The amount of amides and waxes used will be 0.1-5% by weight.

[0078] Erucamide may be used as a slip agent. The amount of stearate used is 0.1-5% by weight.

[0079] Lignin itself can not only increase the water repellency of the composite material, but also increase the mechanical durability of the composite material. The amount of lignin is 0.1-2 wt%.

[0080] Based on the above, in one embodiment the material of the wall of the container is one or more additives selected from the group of metal stearates such as zinc stearate and calcium stearate, maleic anhydride grafted thermoplastics, oleamide, erucamide, fatty acids, wax lignin and mixtures thereof, incorporating one or more additives in an amount of up to 10% by weight, in particular about 5% by weight.

[0081] Typically, the additive is incorporated into the mixture of biodegradable polymer and wood chips in an amount of up to 10% by weight, particularly about 5% by weight, before the mixture is processed to form a container.

[0082] It is preferred that the wood particles are distributed throughout the thermoplastic polymer matrix, and more preferably, the wood particles are uniformly distributed throughout the thermoplastic polymer matrix. In compost, the material degrades, usually completely, in the presence of swollen wood chips. In one embodiment, uniform distribution means that the wood particles are distributed throughout any 1 cm of the material. 3The wood particle content in the volume of 1 cm 3 It means that the average content of the other 10 volumes of material has less than 50% of the volume of the composite. In a preferred embodiment, the composite material formed from a translucent polymer and molded into a plate having a thickness of 2.5 mm is non-translucent due to the presence of wood particles therein, especially when the content of wood particles is more than 30% of the total weight of the wood particles and the thermoplastic polymer, especially when it is 40% or more.

[0083] The matrix of the composite material is usually formed by a biodegradable thermoplastic polymer. In one embodiment, the thermoplastic polymer has a melting point of more than about 150°C, particularly more than about 155°C. The thermoplastic polymer may be a biodegradable polymer, such as polyesters, particularly those containing poly(hydroxy acids). Thus, the polymer may be selected from the group of biodegradable polymers comprising polylactides and poly(lactic acids), polyglycolides and poly(glycolic acids), cellulose acetate propionates, and polyhydroxyalkanoates, such as polyhydroxybutyrate, and mixtures thereof. Non-biodegradable polymers such as polyolefins, polyesters, particularly biodegradable polyesters, polyamides, polyimides, etc., may also be used to achieve composites filled with wood particles, as described herein. The molecular weight of the biodegradable polymer should be high enough to allow entanglement between the polymer molecules, and low enough to be melt processed.

[0084] In one embodiment, polylactic acid or polylactide (both referred to by the abbreviation "PLA") is used. One particularly preferred embodiment involves using a PLA polymer or copolymer having a weight average molecular weight of about 10,000 g / mol to about 600,000 g / mol, preferably less than about 500,000 g / mol or about 400,000 g / mol, more preferably about 50,000 g / mol to about 300,000 g / mol or about 30,000 g / mol to about 400,000 g / mol, and most preferably about 100,000 g / mol to about 250,000 g / mol, or about 50,000 g / mol to about 200,000 g / mol.

[0085] When PLA is used, it is preferred that the PLA is in semi-crystalline or partially crystalline form. To form semi-crystalline PLA, it is preferred that at least about 90 mole percent of the repeating units in the polylactide are either L- or D-lactide, and even more preferably at least about 95 mole percent. In another embodiment, the thermoplastic polymer has a melting point in the range of about 110 to 120°C. Such thermoplastics can be selected from polybutylene adipate terephthalate (abbreviated PBAT).

[0086] Thermoplastic polymers may comprise neat polymers in the form of either homopolymers or copolymers, e.g., random copolymers such as a copolyester of adipic acid, 1,4-butanediol, and dimethyl terephthalate. PBAT polymers are typically biodegradable, statistical, aliphatic-aromatic copolyesters. Suitable materials are supplied by BASF under the trade name Ecoflex®. The polymer properties of PBAT are similar to PE-LD due to the high molecular weight and long chain branched molecular structure.

[0087] PBAT is classified as a random copolymer due to its random structure. This also means that it cannot crystallize to any significant degree, since there is a widespread absence of any kind of structural order. This leads to some physical properties, namely a broad melting point, low modulus and stiffness, but high flexibility and toughness. In addition to virgin polymers, the composition may also contain recycled polymeric materials, especially recycled biodegradable polymers. Furthermore, the composition may also contain composites of polyesters such as fiber-reinforced PLA, ceramic materials and glass materials (e.g., bioglass, phosphate glass).

[0088] Based on the above, one embodiment provides a material having a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix and mixing therein particles of hydrophilic material capable of swelling in the matrix upon absorption of water, and at least one second layer of compostable material comprising a biodegradable polymer forming a continuous matrix and not containing particles of hydrophilic material capable of swelling in the matrix. The at least one biodegradable polymer of the first layer and the second layer and further layers is preferably selected from polylactides and poly(lactic acid), polyglycolides and poly(glycolic acid), cellulose acetate propionate, and polyhydroxyalkanoates. The material can be formed into a product, such as a layered product capable of forming an article or a part thereof (such as the wall of a container), the product having a thickness of more than 1 mm, in particular more than 1.2 mm, up to 25 mm or more, usually less than 50 mm. The layered product is decomposable under industrial composting conditions.

[0089] In one embodiment, the material is used in packaging articles, particularly containers such as jars, for a variety of materials, including water-based and oil-based products.

[0090] In one embodiment, the method for producing a composite material comprises the step of providing a thermoplastic polymer having a melting point above 110°C, in particular above 120°C, for example above 130°C, in particular above 150°C or above 155°C. In one embodiment, the melting point is 320°C or less, for example below 250°C, in particular below 230°C. Preferably, the thermoplastic polymer is a biodegradable polymer, providing non-fibrillated wood particles, at least a portion of the wood particles, having a sieving size of more than 0.5 mm, melt mixing the thermoplastic polymer with the wood particles in a mixing ratio of 35:65 to 80:20 by weight to form a composite melt, and cooling the melt. In one embodiment, such a thermoplastic polymer is a biodegradable polymer having a melting point above 110°C, in particular above 150°C or above 155°C.

[0091] The cooling step is preferably carried out in a mould where the melt is shaped into an article having a predetermined shape. Typically, the thermoplastic polymer is fed in the form of finely divided particles or pellets together with the non-fibrillated wood particles in the form of a dry mixture into a feed zone of the melt-processed polymer processing device. The thermoplastic polymer is fed in the form of a neat polymer, as a homopolymer or copolymer. Further embodiments include the steps of (providing a slate-like mineral pigment; and) melt-mixing the mineral pigment with the wood particles and the thermoplastic polymer, the amount of mineral pigment being 0.1-40% by weight, calculated from the total weight of the thermoplastic polymer and the wood particles.

[0092] A blend or mixture comprising a thermoplastic polymer, wood particles, and mineral pigments like slate is processed by injection molding into a predetermined article. In one embodiment, the components are physically mixed and fed into a hopper of an injection molding machine having a screw mixing zone. To reduce or prevent degradation of the polymer, the components are exposed to melt mixing in the screw for a limited time, usually corresponding to less than about 10 minutes. The processing temperature is kept below the decomposition temperature of the polymer. For PLA, a maximum temperature of 230°C is preferred. To reduce or prevent degradation of the polymer during processing, in a preferred embodiment, a screw with an L / D ratio of at least 20:1 is used. A mold is used to shape the melt into an article of a predetermined shape. The mold temperature is generally below the glass transition temperature of the polymer. For PLA, a temperature of about 25-60°C is preferred, and for amorphous PLA, the preferred range is about 35-55°C. The pressure used during injection moulding is usually in the range of from 50 to 150 bar, for example about 80 to 120 bar, with a back pressure in the range of from 50 to 100 bar.

[0093] During melt processing, it is generally preferred to maintain the temperature below the decomposition temperatures of the polymeric material and the wood components. Thus, in a preferred embodiment, the material is treated at temperatures below 230°C, especially below 220°C.

[0094] The thermal properties of the composition can be modified and improved by the addition of mineral components. Thus, the use of slate-like mineral pigments such as talc or clay not only improves the barrier properties but also improves the heat resistance. This allows the mixing and processing of the wood particles with the polymer without pyrolysis of the wood particles even at temperatures above 200oC.

[0095] The composite material exhibits combined gas, liquid, and oil barrier properties. Although the material itself has good properties, the barrier properties of the molded article can be further improved by applying a barrier coating to the surface of the melt. In particular, the coating is applied to the surface of the cooled melt or to the surface of an article molded from the composite material.

[0096] The coating can be produced by multi-component injection molding. A common example of such a method is the two-component (hereinafter also abbreviated as "2K") processing method, preferably by 2K injection molding from exactly the same material as used to produce the container. The adhesion between the two layers made of the same material is ideal and no seams are visible. With a polymer coating layer thickness of 0.8 mm, the coated container shows the same water repellency as 100% polymer by weight.

[0097] Multi-component injection molding can also include three, four or more component molding (3K, 4K, etc. molding).

[0098] Based on the above, in one embodiment, a method for producing a container for a cosmetic product having a wall formed by a first layer of a compostable material comprising a biodegradable polymer forming a continuous matrix in combination with particles of a hydrophilic material mixed therein that can swell within the matrix upon absorption of water, and by a second layer of a compostable material comprising a biodegradable polymer forming a continuous matrix and containing less or substantially no particles of a hydrophilic material that can swell within the matrix upon absorption of water, comprising: forming a first mixture including a biodegradable polymer that forms a continuous matrix and has mixed therein particles of a hydrophilic material that is capable of swelling within the matrix upon absorption of water; forming a second mixture comprising a biodegradable polymer that forms a continuous matrix and has a reduced content of particles of a hydrophilic material that is capable of swelling within the matrix upon absorption of water; and processing the first and second mixtures by injection molding to form a container wall comprising layers of the first and second mixtures in an overlapping arrangement, e.g., the first and second mixtures are processed to form a multi-layered "sandwich" type wall structure.

[0099] In a second embodiment, a method of making a shaped article, such as a container, having a wall formed by a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix in combination with particles of a hydrophilic material mixed therein that can swell within the matrix upon absorption of water, and by a second layer of compostable material comprising a biodegradable polymer forming a continuous matrix and not including particles of a hydrophilic material that can swell within the matrix upon absorption of water, comprising: forming a first mixture including a biodegradable polymer that forms a continuous matrix and has mixed therein particles of a hydrophilic material that is capable of swelling within the matrix upon absorption of water; forming a second mixture comprising a biodegradable polymer that forms a continuous matrix and has a reduced content of particles of a hydrophilic material that is capable of swelling within the matrix upon absorption of water; processing the first and second mixtures by injection molding to form a container wall comprising layers of the first and second mixtures in an overlapping arrangement, e.g., the first and second mixtures are processed to form a multi-layered "sandwich" type wall structure; wherein the biodegradable polymer of at least one of the first and second layers and any further layers is selected from polylactides and poly(lactic acid), polyglycolides and poly(glycolic acid), cellulose acetate propionate, and polyhydroxyalkanoates.

[0100] The second layer temporarily protects the first layer from contact with water, delaying the onset of wall degradation. For example, if the second layer is composed of a thermoplastic biopolymer without swellable wood particles, such as pure PLA, the composite first layer will not come into contact with water until it has penetrated the PLA layer. The length of time required for water penetration depends on the thickness and temperature of the second layer, but typically a period of up to 12 months is possible.

[0101] The properties of the product have been found to be influenced by the topography of the composite material used in the product. Furthermore, it has been found that the greater the surface roughness, the higher the water absorption value of the WPC. This will accelerate the biodegradation of the material and increase the rate of biodegradation. It has also been observed that the higher the wood content, the higher the surface roughness of the WPC. This is due to the higher amount of wood present on the surface of the injection moulded part.

[0102] Thus, in one embodiment, the above-mentioned second layer is provided to be free of wood or other natural materials in the polymer, such that the biodegradation rate of the polymer component, such as PLA or another biodegradable polymer, is slowed down due to the smoother surface of the piece made from pure polymer.

[0103] In one embodiment, the surface of the second layer opposite the first layer is smooth. In this context, "smooth" means a surface with a surface roughness (Ra) of less than 1 μm, determined according to ISO 4287. The surface of such containers is typically made of wood-PLA composites containing less than 30% by weight of wood and is stable against water and ethanol absorption for up to 6 months.

[0104] In contrast, tests have shown that containers made of wood-PLA composites containing more than 30% by weight of wood particles and with Ra values ​​determined to ISO 4287 of more than 1.1 μm rapidly absorb water and are not stable against absorption of water and ethanol for 6 months when they form the inner surface of the bottle.

[0105] As the example below shows, containers made of wood-PLA composite and with injection moulded container walls meet the requirements for composting according to ISO 4287 when the inner surface roughness is ≥ 0.4 μm and the outer surface roughness is ≥ 2.0 μm (tested for 12 weeks in an aerobic industrial compost according to the framework specified in ISO 13432).

[0106] Based on the above, in one embodiment, the surface of the second layer that faces either the interior of the container or the exterior of the container is free or substantially free of visible wood particles. Such a layer is

[0107] Additionally, in one embodiment, the surface of the layer facing the interior of the container contains up to 10% by weight of wood particles.

[0108] At high temperatures, the water absorption levels of the compositions studied herein constituting the first layer were between 3 and 4% by weight in the first week. The difference in water absorption increased dramatically during the one-month test period. The best results from a composting point of view were achieved with a compound containing PLA modified with zinc stearate and maleic anhydride, which improves the surface quality of the molded bottles.

[0109] Surface quality depends heavily on the moisture content of the raw material before injection molding. If the processing temperature of the polymer is close to 200°C, the moisture level present in the polymer can cause problems because at this temperature (100°C), water boils out of the polymer. When the water boils, steam in the form of bubbles is trapped inside the molded part. When the molded part cools and solidifies in the mold, splay marks are created on the finished product. Wood is also a problematic material in the molding process. At injection molding temperatures of 180°C to 220°C, volatile organic components (VOCs) in wood, such as terpenes and their derivatives, α-pinene and β-pinene, and low molecular weight aldehydes, can cause microbubbles in the produced product and high water absorption during use. Furthermore, the pyrolysis reaction of wood can cause the formation of fatty acids such as acetic acid, which can cause corrosion of parts of the mold and reduce the quality of the surface smoothness.

[0110] In one embodiment, the amount of moisture ("moisture content") in the wood particles, e.g., wood chips, should be reduced to less than 250 ppm, e.g., less than 50 ppm, in particular less than 30 ppm, and the moisture content in the PLA prior to injection molding should be reduced to less than 500 ppm, in particular less than 250 ppm, respectively.

[0111] In one embodiment, low moisture levels in wood are achieved by drying wood material, such as wood chips, in a vacuum at 105°C for 4 hours. In one embodiment, which can be combined with the previous embodiment, the polymer granules are dried, for example in a desiccant air dryer, at a temperature close to, but preferably below, the glass transition temperature for 1-12 hours. Thus, in the case of PLA, the polymer in granular form is dried, for example, in a desiccant air dryer at 60°C for 4 hours.

[0112] Injection molding is one of the most common processing techniques in the plastics industry. It is a high-speed process used to manufacture large numbers of identical three-dimensional products. Parts are produced by injecting molten plastic into a mold and allowing it to cool.

[0113] Generally, the injection molding of wood-PLA-composites with various contents of wood particles can be carried out as follows:

[0114] The material is fed from a hopper into a heated barrel, whose temperature is controlled according to the plastic specifications to melt the material. The rotational movement of the screw in the barrel section moves the melt through the machine. Furthermore, the screw of the injection molding machine provides heat, mixes the material, and maintains the injection pressure. The molten material is transported from the barrel section into a runner system, from which the molten plastic is injected into a cooled mold to form the final product, and the material is cooled.

[0115] In one embodiment, the raw material components, after drying, for example as described above, are fed separately into an injection molding line hopper.

[0116] In single-component injection molding, only one type of material is used to manufacture a product. However, there are several techniques for creating parts containing multiple materials. Multi-component injection molding is one example. In multi-component molding, two or more materials can be used in the same part. The materials are injected into the same mold from two (or more) barrels.

[0117] Wood has a tendency to burn at high temperatures, especially when combined with polymers such as PLA, which have a melting point close to 180°C. It has been found that combustion can also occur when processing wood and polymer mixtures, where the wood raw material comprises both sieved wood chips with a size greater than 1 mm and wood flour, which typically has a sieved size of 100 micrometers or less. The shear rates in such mixtures are high and become inhomogeneous, compromising the structural properties of the product formed by injection molding. In the gate area, hot zones can form in the material, where increased friction causes the wood to burn and discoloration and decomposition of the polymer component (thermoplastic material).

[0118] Therefore, in one embodiment, the injection molding of the wood-polymer mixture to form the wood-plastic composite is carried out by avoiding the formation of hot zones within the material.

[0119] In one embodiment, injection molding is carried out by maintaining a uniform shear rate within the injected material.

[0120] In one embodiment, the injection molding is performed using a needle gate system.

[0121] In one embodiment, the injection mold and hot runner system are dimensionally adapted specifically to the feedstock material. For example, the injection mold and hot runner system may have a sieve size in the range of 1-2 mm, typically 12.25 cm. 3 5 to 25 cm 3 For PLA pellets and wood particles intended to produce thick-walled objects such as bottle caps with a volume of 100 mm, the preferred minimum size of the nozzle gate diameter is 2.5 mm, and the corresponding minimum diameter of the hot runner system is 9 mm. Such dimensions will improve the flow of the wood particle containing material through the hot runner system.

[0122] In one embodiment, the biodegradable polymer, such as PLA, is present in the final product in an amorphous state. Providing the biodegradable polymer, such as PLA, in an amorphous state is beneficial for achieving rapid degradation of the material. It is also beneficial for aesthetic reasons.

[0123] In one embodiment, the mold temperature during molding of the material is kept below the glass transition temperature of the biodegradable polymer. g For PLA, the mold temperature is typically kept below 60° C. In one embodiment, for PLA, the mold temperature is kept between 25-40° C. By keeping the temperature of the material below the glass transition point, the biodegradable material can be maintained in an amorphous state.

[0124] In one embodiment, the cavity of the mold used for injection molding is completely filled during the injection stage. Preferably, the mold is filled by feeding the molten polymer to the mold by injection molding with a laminar flow, in particular a laminar flow with a wide flow front.

[0125] In one embodiment, injection molding is performed by avoiding flowing streams.

[0126] Mold filling can be divided into fountain flow and solid flow. Fountain flow is typical for thermoplastic polymers. It is the result of the melt contacting the mold wall and occurs due to a parabolic flow front.

[0127] The outer skin of the plastic in contact with the cold mold freezes rapidly, while the central core remains molten. As additional material is injected, it flows into this central core, displacing the material already there and forming a new flow front. This displaced material flow is a combination of the forward flow and the outward flow. The outward flow contacts the wall and freezes, forming the next section of the skin, and the forward flow forms the new molten core.

[0128] The frozen layer is formed by the expansion of the flow front, which results in low shear stresses and a very low level of molecular orientation. Initially, the frozen layer is very thin, so heat is lost very rapidly.

[0129] Solid flow is typical for highly filled polymeric compounds and thermosetting resins. It causes the melt to slide over a layer of lower viscosity resin. The flow front consists of a less compact melt followed by a compact melt zone. No orientation of the reinforcing particles is possible.

[0130] Additional polymer layers on wood composites can be produced using the 2K injection molding technique. One of the main advantages of 2K injection molding compared to overmolding is that the polymer being injected is still hot and has not yet shrunk. This practically eliminates the risk of burn-out formation in the second component. Furthermore, the surface remains "virginally" clean, allowing good molecular adhesion. Another important advantage is the resulting cycle time, the constant process and the fact that no manual insertion is required, thus avoiding the risk of damaging the first component. With the 2K technique it is possible to create multi-layered "sandwich" type structures.

[0131] Overmolding is a proprietary injection molding process that seamlessly combines multiple materials into one part or product. The composite bottle is covered with a thin outer layer using either single-shot (insert molding) and two-shot (multi-shot molding) techniques.

[0132] According to one embodiment, the injection molding of the wood biodegradable polymer composite is carried out using the following main processing parameters:

[0133] Injection molding processing conditions Throat 40-60°C Feed Zone 150-160°C Compression Zone 160-170°C Homogenization zone 175-190°C Machine nozzle 175-190°C Back pressure 50-100bar Hot runner nozzle 200-220°C and extrusion 20-25°C T mold ,Front 40-45°C T mold ,Back Optimization may be required in typical settings. General advice for both cold and hot runners

[0134] The material is suitable for producing containers such as hard or semi-rigid walled containers for cosmetics or food, the contents of which may be cold or warm, typically the contents may have a temperature of 0-100°C, for example 1-80°C, although the containers may also be used in sub-zero conditions. In one embodiment the containers may be used at -45°C...-0°C, in particular -25°C...-0°C.

[0135] According to the experimental results described herein, improved compostability properties are achieved by blending biodegradable polymers, exemplified by PLA, with natural materials.

[0136] Specific embodiments of the present invention will now be described with reference to examples. The following non-limiting examples are illustrative of embodiments of the present technology and should not be construed as limiting the scope of the present invention. EXAMPLES

[0137] The polymer and wood chips were dried in a desiccant dryer at 100–105 °C for 4 h before being fed into the hopper of the injection molding machine.

[0138] The polymer comprised PLA containing greater than 99% PLLA isomer and less than 1% PDLA isomer.Wood chips were selected to have physical dimensions of approximately 2mm x 1mm x 1mm.

[0139] To ensure that the product quality meets requirements, the moisture content of the raw materials was reduced to less than 250 ppm.

[0140] Within the hopper, the dry material was fed into the barrel section of the injection molding machine, where the temperature was set at 155-185°C. The molten mixture of wood chips and polymer was then fed into a hot runner system, where the temperature was set at 195-210°C. The material was then injected into the mold, where the temperature was set at 25-40°C to ensure efficient cooling. The back pressure of the machine was set at 50-100 bar.

[0141] As will be seen below, the parts manufactured in the form of containers were tested for compostability and other properties.

[0142] The compostability of the product was measured under practice-relevant conditions (disintegration) for 12 weeks in an aerobic industrial compost according to the framework given in the ISO 13432 standard. Product degradation was evaluated using the disintegration method. To investigate the compostability of the wood composites, cosmetic bottles with a diameter of 7 cm, height of 3 cm and a maximum wall thickness of 8 mm were injection moulded using the following composite recipe:

[0143] [Table 1]

[0144] Figures 2a to 2c show photographs of the three sample jars before the composting test.

[0145] Briefly, the jars were inserted inside stainless steel capsules containing compost material and buried in an industrial compost for 12 weeks. The changes in the samples were examined at the beginning, twice during the composting period and once after the composting period. The dry mass of the samples was measured and the disintegration of the samples according to ISO16929 was defined at that time. The capsule contents, including the disintegrated samples, were sieved after the test.

[0146] The results showed that the samples disintegrated under the conditions employed in industrial composting facilities. After 17 days of composting, all nine samples disintegrated into fragments and no measurable dry mass was obtained. During the 12-week test period, all samples disintegrated into fragments between 1 and 2 mm in size, leaving the six control plastic samples unchanged. The results of the sieving test support the assumption that 90% of the samples disintegrated to particle sizes less than 2 mm, sufficient to reach the industrial composting environment in 12 weeks.

[0147] FIG. 3 shows a photograph showing the decomposition of sample Com-2 in industrial compost.

[0148] The results show that wooden composite bottles with thick walls (up to 8 mm) made from this material meet the EN13432 standard requirements for disintegration and volatile solids content, which can be considered a significant improvement when compared to previous compostability results of existing PLA-based blends with a maximum wall thickness of 1.2 mm, which exceeds the standard requirements.

[0149] The properties of this bottle made from a PLA / wood blend (hereafter referred to as "Sula") meet the quality requirements of cosmetic packaging and offer significantly improved compostability over existing PLA-based blends. This is achieved by the combination of specially sized wood chips and a biodegradable polyester matrix. The swelling of the wood particles during water absorption accelerates the cracking and fragmentation of the polymer matrix. For now, the wood particles are small enough to produce sufficient mechanical, physical and chemical properties for the bottle to support its use as cosmetic packaging. Smaller particles, i.e. sawdust, would not efficiently enhance the compostability through water absorption and swelling, while larger particles would cause obstacles in the manufacturing process and overly fix the decomposition.

[0150] In-house testing at normal room temperature and pressure conditions involved filling the bottles with water and tracking the effect of weight gain on bottle collapse, swelling, and aesthetics (Table 2). Each sample set consisted of three bottles.

[0151] A schematic diagram of the bottle used in the water intake test is shown in Figure 4, which shows the cross section of the bottle used in the water intake test.

[0152] As shown, the bottle is composed of a base and a cap. The thickness of the base is 3.5 mm, and the wall thickness of the threaded portion is 4.1 mm and 2.3 mm. The internal surface area of ​​the bottle investigated above is approximately 40 cm. 2 It is.

[0153] [Table 2]

[0154] The pure PLA jar (sample 1) absorbed only 0.4% by weight of water over one month. No physical or aesthetic changes of the jar were detected. When the jar contained 10% by weight of wood chips, the water absorption increased slowly to the level of 1% by weight and was completed there over the course of one month. The water absorption of the jar with 40% by weight of wood chips increased to the level of 5% by weight, causing strong dimensional changes and the jar was leaking from the bottom. The jar was full of cracks but remained in one piece. Surprisingly, the sample containing 40% by weight of wood chips with a sieving size of 0-1 mm absorbed only 3% by weight of water without any change in appearance.

[0155] The tests clearly show that pure PLA bottles do not biodegrade or disintegrate within a few months at room temperature. The amount of wood chips and chip size have a crucial effect on the degradation characteristics of the bottle products investigated here.

[0156] When the wood weight percentage of the jar material is less than 30 wt%, the water uptake is very slow and remains below 3 wt% within 30 days. A similar phenomenon was detected when sawdust was used as a filler (sample 6). No collapse was detected even when the jar contained 40 wt% wood. The sawdust is not capable of sufficient swelling that could destroy the PLA matrix around the wood chips. Also, the jar made with compounded pellets containing 40 wt% wood showed a lower water uptake by 1 percentage point compared to sample 5 made with non-compounded wood. The lower water absorption of compounded jars is related to the reduction in the size of the wood chips during the extrusion-based compounding process. It should be noted that compounding does not affect the properties of PLA (such as molar mass value).

[0157] FIG. 5 shows the water absorption of the bottles in weight percent.

[0158] The water absorption rate of sample set 5 (40% wood by weight) was 1.5g / 33 days / 40cm 2 →1.13mg / (day cm 2 ) and the water absorption rate of sample set 3 (20% wood by weight) was 1.09g / 33 days / 40cm 2 →0.82mg / (day cm 2 For pure PLA, the absorption value was only 0.08g / 33 days / 40cm 2 →0.061mg / (day cm 2 ) was.

[0159] The room temperature tests described above were also carried out at 50 °C, which mimics industrial composting conditions. As the temperature increased from 22 to 50 °C, the water uptake of the pure PLA bottle increased from 0.11 to 0.5. Water uptake was four times faster at the higher temperature. The increase in water absorption rate for the wood containing bottle was slightly lower, about 3.5 times faster from the initial value.

[0160] FIG. 6 is a bar graph showing water intake as a percentage of bottle weight over the one week study period.

[0161] A rough extrapolation of the water uptake over 12 weeks based on the above results indicates that at 50°C, a bottle made of pure PLA has a water uptake of about 6% by weight, and with 10% by weight wood, the water uptake is about 11% by weight. For a bottle containing 30% by weight wood, the estimated water uptake is already as high as 43%. In our in-house tests, a bottle that absorbed 15% by weight of water remained in one piece.

[0162] Total migration tests were used to investigate how inert materials are in contact with different simulants by filling methods according to EN1186-9 and EN1186-14. Aqueous simulants such as 10% ethanol, 3% acetic acid and 50% ethanol were used. Of these, acetic acid simulates conditions below pH 4.5 and 50% ethanol simulates partially lipophilic conditions such as water-oil emulsions. Instead of vegetable oils, non-polar solvents were used to simulate fatty foods; namely 95% ethanol and isooctane were used. The test conditions selected were 10 days at 40°C (except for isooctane at 20°C for 2 days), which corresponds to long-term storage at or below room temperature, including heating up to 70°C for up to 2 hours or heating up to 100°C for up to 15 minutes. According to Regulation (EC) 10 / 2011 on plastic materials intended for contact with food, a total migration of 10 mg / dm 2 should not exceed .

[0163] The results in Figure 6 show that the bottle made of plain PLA was inert under the test conditions in contact with all simulants. Wood composites with 10-20 wt% wood (Sula10 and Sula20) were nearly as inert as PLA in contact with all simulants. The composite with 30 wt% wood (Sula30) showed only slight reactivity with the emulsion simulant 50% ethanol, while the composite with 40 wt% wood (Sula40) showed increased reactivity with all aqueous simulants, especially 50% ethanol and 3% acetic acid.

[0164] The layered wall structure sample cups were fabricated using two-component (2K) injection molding. Both sandwich and two-wall techniques were used.

[0165] In one embodiment, the sandwich method was used to produce a wall with three layers, the outermost and innermost layers being of the same material with a layer of a second material sealed between them. In this case, the outermost and innermost layers were PLA and the intermediate layer between them was a wood composite material (in the specific example, "Sula 20" and "Sula 30", respectively). Thus, the wood composite layer was completely surrounded by a layer of PLA on all sides. In one embodiment of the sandwich method, the PLA layer had a thickness of 0.5 to 1 mm, in particular about 0.8 mm.

[0166] The two-wall method produced only two layers: a PLA layer on the inside of the cup and a wood composite layer on the outside. This method resulted in thicker layers; in this particular case, the PLA layer was about 1 mm thick.

[0167] As can be seen from Table 3, both methods were used successfully to restore inertness comparable to plain PLA with all simulants, where both layer thicknesses were equally effective.

[0168] [Table 3]

[0169] Based on the migration results and microscopy images (Figure 7) of the Sula40 material surface, it was concluded that the inertness of the material is greatly affected by the exposure of wood particles on the surface. Without a protective layer of polymer on top of the wood particles, the particles are directly exposed to the simulant and are more susceptible to moisture ingress. As shown in the migration data, the percentage of wood particles exposed on the surface directly affects the absorption behavior of the material. The higher the wood content, the higher the absorption. However, a 0.8mm protective layer of PLA on top of the wood composite layer showed a decrease in absorption.

[0170] In the present invention, the balance between biodegradation and inertness is controlled by the surface exposure of the wood particles to a protective PLA layer on the surface.

[0171] Figures 7a and 7b are microscopic images of a Sula 40 wood composite sample: Figure 7a shows the surface and Figure 7b shows the cross section after contact with Oil Red O stained water at 23°C for 94 days.

[0172] The image shows that the wood particles are exposed on the surface (stained red). The cross-sectional image shows that only the surface wood particles have come into contact with the dyed water and stained red, whereas the wood particles inside the wall have not absorbed the dyed water.

[0173] The smoothness of the bottle surface has a significant effect on the water absorption rate and degradation rate of the composite. Treatments such as plasma, which are traditionally used to improve adhesion between the coating and core materials, have been shown to reduce water absorption levels to 1.66 mg mg / (day cm 2 ) and within two weeks the jars were filled with water.

[0174] Five bottles manufactured as described above, but with wood contents ranging from 0 to 40 wt. % and, in some cases, additionally containing white pigment (PCC), were analyzed for surface smoothness.

[0175] Surface smoothness was determined according to ISO 4287 using a Wyko NT9100 optical profiling system.

[0176] The surface roughness values ​​of the test materials were obtained when the mold temperature was below 50°C.

[0177] The mold itself has a VDI roughness value of 20-30, which corresponds to 1-3 micrometers (Ra).

[0178] The results are shown in Figure 8, and SEM micrographs of the surfaces of various samples are shown in Figures 9A to 9D.

[0179] As can be seen from the bar graph in Figure 8, for the neat PLA polymer, the roughness of the inside surface ("inside") of the container was about 0.35 μm, and the outside surface ("outside") was about 2.05 μm. These values ​​reflect the corresponding roughness values ​​of the mold. The surface of the mold that matches the outside surface of the bottle is

[0180] For wood-PLA composites, the roughness increases with the wood content. This is represented by the first three sets of bars. For 10% of the wood particles, calculated from the total weight of the wood-PLA composite, there is a slight increase, above 0.4 μm on the inside and 2.1 μm on the outside. For 30% wood, the roughness is already above 1 μm on the inside and 2.3 μm on the outside. For 40% wood, the roughness is about 1.2 μm on the inside and about 3.15 μm on the outside. By adding about 5% PCC, the roughness on the outside can be somewhat reduced, as can be seen from the fourth set of bars. Thus, the roughness on the inside is about 1.25 μm, but the roughness on the outside is about 2.3 μm.

[0181] The micrographs in Figures 9A-9D show how the inner surface texture changes depending on the wood content (wood particle content).

[0182] During composting, a fast water absorption rate is a beneficial feature, but not when, for example, cosmetics need to be stored in a jar for 12 months before use. The migration results for 50 wt% ethanol interestingly revealed that a thin layer of polymer on the surface of the jar reduced migration to an acceptable level (Table 3). The same results were obtained when the wood content of the composite was reduced to 30 wt%. The wood chips in a jar containing 40 wt% wood are close to the surface and when in direct contact with the liquid, the chips start to swell within a few weeks, microcracks form, and eventually the jar rapidly decomposes. Furthermore, if the wood content is reduced or the size of the wood chips is too small, the swelling only causes minor cracks in the polymer matrix and no structural collapse can occur.

[0183] Based on the results of the roughness test and taking into account the degradation tests carried out, it can be concluded that the bottles made of the present wood-PLA composite meet the requirements for composting when the surface roughness values ​​are greater than 0.4 for the inner surface of the container and greater than 2.0 μm for the outer surface of the container, according to the embodiment of the test.

[0184] Several embodiments of the present technology are disclosed below.

[0185] 1. A compostable wood composite material formed by a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix in combination with particles of a hydrophilic material capable of swelling within the matrix upon absorption of water mixed therein, and by a second layer of compostable material comprising a biodegradable polymer forming a continuous matrix and free or substantially free of particles of a hydrophilic material capable of swelling within the matrix or having a substantially lower content of such particles than the first layer.

[0186] 2. The material according to embodiment 1, wherein the particles of hydrophilic material capable of swelling within the matrix upon absorption of water are selected from particles obtained by mechanical processing of wood or other lignocellulosic materials such as annual or perennial plants and plant residues.

[0187] 3. The material according to embodiment 1 or 2, wherein the thickness of the first layer is greater than the thickness of the second layer, in particular the ratio of the thickness of the first layer to the thickness of the second layer is about 1.1:1 to 100:1, for example 1.2:1 to 10:1.

[0188] 4. The material according to any of the preceding claims, wherein the first layer comprises 5 to 50% by weight, in particular 15 to 40% by weight, of particles of hydrophilic material, calculated on the total weight of the first layer.

[0189] 5. The material of any of the preceding claims, wherein the biodegradable polymer of at least one of the first, second and third layers is selected from the group of biodegradable polyesters, such as polyesters including polylactides and poly(lactic acid), polyglycolides and poly(glycolic acid), cellulose acetate propionate, or polyhydroxyalkanoates, e.g., polyhydroxybutyrate.

[0190] 6. The material of any of embodiments 1 to 5, which meets the following specifications: in compost, biodegradation of the material at 58°C occurs within a period of up to 6 months, the level of biodegradation reaches a level of 90% of the total weight of the layer, and disintegration of the layer at 58°C occurs within 12 weeks.

[0191] 7. The material according to any of the preceding claims, wherein the first layer comprises coarse wood particles mixed with the biodegradable thermoplastic, and the moisture content of the wood particles, e.g. wood chips, has been reduced to less than 250 ppm, e.g. less than 50 ppm, in particular less than 30 ppm, prior to mixing with the biodegradable thermoplastic.

[0192] 8. A material according to any one of embodiments 1 to 7, formed into a product, such as a layered product, having a thickness of more than 1 mm, in particular more than 1.2 mm, up to 25 mm or more, preferably a layered product that is decomposable under industrial composting conditions. [Industrial Applicability]

[0193] The product can be used as packaging and containers, such as lidded bottles, for various materials, including water-based and oil-based products. Such products are exemplified by food products, cosmetics and pharmaceutical products, especially those that contain or consist of oils, emulsions, creams and gels.

[0194] The products are also suitable for storing or serving natural or cooked products containing sugar such as honey, jams, etc. They may further be used for dry substances such as milk powder or powdered milk (condensed milk, milk powder), dried fruit, soups, meat, fish, spices, tea, cocoa, coffee, etc., which are provided in the form of powdered or dried natural or cooked or otherwise prepared ingredients, to name a few. [Prior art documents] [Patent documents]

[0195] [Patent Document 1] U.S. Patent No. 8,722,773B1 [Patent Document 2] JP2002113822A [Patent Document 3] International Publication No. 2015 / 049589 (WO2015 / 048589A1) [Patent Document 4] Chinese Patent Application Publication No. 101712804 (CN101712804A) [Patent Document 5] U.S. Patent Application Publication No. 2013 / 253112 (US2013 / 253112A1) [Patent Document 6] U.S. Patent Application Publication No. 2016 / 076014 (US2016 / 076014A1) [Patent Document 7] U.S. Patent Application Publication No. 2002 / 130439A1 [Patent Document 8] European Patent Application Publication No. 0319589 (EP0319589A) [Patent Document 9] U.S. Patent Application Publication No. 2018 / 215972 (US2018 / 215972A1) [Patent Document 10] Chinese Patent Application Publication No. 107932874 (CN107932874A) [Patent Document 11] JP2010280152A [Patent Document 12] US Patent Application Publication No. 2006 / 0267238 (US20060267238A1) [Patent Document 13] U.S. Patent No. 6,210,792 (US6,210,792B1) [Patent Document 14] U.S. Patent No. 6,632,863 (US6,632,863B2) [Patent Document 15] Canadian Patent Application Publication No. 1171656 (CA1171656A) [Patent Document 16] International Publication No. 2015 / 049589 (WO2015 / 048589A1) [Non-patent literature]

[0196] [Non-Patent Document 1] Kale, G., Kijchavengkul, T., Auras, R., Rubino, M., Selke, SE, Singh SP “Compostability of Bioplastic Packaging Materials: An Overview.” Macromolecular Bioscience 7(2007), 255-277.

Claims

1. a first layer of compostable material comprising in combination a biodegradable polymer forming a continuous matrix and particles of a hydrophilic material mixed therein capable of swelling within said matrix upon absorption of water, said first layer of compostable material comprising 5-50% by weight of said particles of said hydrophilic material calculated based on the total weight of said first layer of compostable material; A second layer of compostable material comprising a biodegradable polymer forming a continuous matrix, said second layer containing less than 50% by weight, calculated based on the total weight of said second layer, of particles of a hydrophilic material capable of swelling within said matrix upon absorption of water. A container having a wall formed by The wall comprising the first layer of compostable material and the second layer of compostable material in an overlapping manner was obtained by multi-component injection molding. container.

2. Container according to claim 1, wherein the particles of hydrophilic material capable of swelling within the matrix upon absorption of water are selected from particles of wood or other lignocellulosic materials selected from annual or perennial plants and plant residues.

3. 3. The container according to claim 1 or 2, wherein said particles of hydrophilic material are derived from natural materials selected from wood or other lignocellulosic materials selected from annual or perennial plants and plant residues.

4. 4. A container according to any one of claims 1 to 3, wherein the particles of hydrophilic material comprise coarse wood particles having a screen size of at least 0.5mm and no more than 25mm.

5. 5. The container according to any one of claims 1 to 4, wherein the wall has a total thickness of between 1 mm and 25 mm.

6. 6. The container of claim 1, wherein the thickness of the first layer is greater than the thickness of the second layer.

7. 7. The container according to any one of claims 1 to 6, comprising at least one third layer of compostable material substantially free of particles of hydrophilic material capable of swelling within the matrix upon absorption of water.

8. 8. The container of claim 7, wherein the compostable material is a biodegradable polymer.

9. A container according to any one of the preceding claims, wherein the first layer comprises 15-40% by weight of particles of hydrophilic material, calculated on the total weight of the first layer.

10. 10. The container of claim 1, wherein the second layer comprises at least 90% by weight of neat biodegradable polymer, calculated based on the total weight of the second layer.

11. the second layer comprises at least 90% by weight of neat biodegradable polymer, calculated based on the total weight of the second layer; and the third layer comprises at least 90% by weight of neat biodegradable polymer, calculated based on the total weight of the third layer; 9. A container according to claim 7 or 8.

12. 12. The container of claim 1, wherein the second layer comprises up to 5% by weight of one or more additives, calculated on the total weight of the second layer.

13. the second layer comprises up to 5 wt. % of one or more additives, calculated on the total weight of the second layer; and the third layer comprises up to 5 wt. % of one or more additives, calculated on the total weight of the third layer; Container according to any one of claims 7, 8 and 11.

14. 14. The container of any one of claims 1 to 13, wherein the biodegradable polymer of at least one of the first and second layers is selected from the group of biodegradable polyesters that are polyesters including polylactide, poly(lactic acid), polyglycolide, poly(glycolic acid), cellulose acetate propionate, or polyhydroxyalkanoates.

15. 14. The container of any one of claims 7, 8, 11 and 13, wherein the biodegradable polymer of at least one of the first layer, the second layer and the third layer is selected from the group of biodegradable polyesters that are polyesters including polylactide, poly(lactic acid), polyglycolide, poly(glycolic acid), cellulose acetate propionate, or polyhydroxyalkanoates.

16. 16. The container according to any one of claims 1 to 15, wherein the container walls meet the following specifications: in compost, biodegradation of the material at 58°C occurs within a period of up to 6 months, the level of biodegradation reaches a level of 90% of the total weight of the wall, and disintegration of the wall at 58°C occurs within 12 weeks.

17. Container according to any one of the preceding claims, wherein the wall contains 10-40% by weight of wood.

18. Container according to any one of the preceding claims, wherein the wall contains 10-30% by weight of wood.

19. 19. The container of any one of claims 1 to 18, comprising a two-ply wall defining a central cavity for receiving contents to be stored in the container, the cavity having an inner surface formed by a second layer and an opposing surface formed by the first layer.

20. 19. The container of any one of claims 1 to 18, comprising a three layer wall defining a central cavity for receiving contents to be stored in the container, the cavity having an inner surface formed by a second layer, an opposing layer formed by a first layer, and an outer layer opposite the first layer to the cavity formed by a third layer.

21. 21. The container of any one of claims 1 to 20, wherein the first layer comprises coarse wood particles mixed with a biodegradable polymer, the moisture content of the coarse wood particles being reduced to less than 250 ppm prior to mixing with the biodegradable polymer.

22. 22. The container of any one of claims 1 to 21, wherein the water content of the biodegradable polymer is less than 500 ppm prior to mixing with the biodegradable polymer.

23. The material of the wall is a metal stearate selected from zinc stearate and calcium stearate; Maleic anhydride grafted thermoplastics; Oleamide; Erucamide; fatty acid; wax; Lignin; dyeing materials selected from natural materials having a stable color up to 200° C.; and Mixtures thereof, 23. The container according to claim 22, comprising one or more additives selected from the group consisting of:

24. 24. The container of claim 23, wherein the one or more additives are incorporated into the mixture of biodegradable polymer and wood particles in an amount of up to 10% by weight, calculated based on the total weight of the mixture of biodegradable polymer and wood particles.

25. 25. The container according to claim 1, wherein the second layer contains less than 25% by weight, calculated on the total weight of the second layer, of particles of hydrophilic material capable of swelling within a matrix upon absorption of water.

26. 26. The container of any one of claims 1 to 25, wherein a surface of the second layer opposite to the first layer has a surface roughness (Ra) as defined by ISO 4287 of less than 1 μm.

27. 27. The container of any one of claims 1 to 26, comprising a first layer of compostable material comprising a biodegradable polymer in combination with particles of a hydrophilic material mixed therein that can swell within the matrix upon absorption of water, the container being formed using injection molding into a container having an inner surface and an outer surface, the inner surface having a surface roughness (Ra) of 0.4 μm or greater and the outer surface having a surface roughness (Ra) of 2.0 μm or greater as determined in accordance with ISO 4287.

28. a first layer of compostable material comprising a biodegradable polymer forming a continuous matrix in combination with particles of a hydrophilic material mixed therein and capable of swelling within the matrix upon absorption of water, said first layer of compostable material comprising 5-50% by weight of the particles of said hydrophilic material calculated based on the total weight of said first layer of compostable material; A second layer of compostable material comprising a biodegradable polymer forming a continuous matrix, said second layer containing less than 50% by weight, calculated based on the total weight of said second layer, of particles of a hydrophilic material capable of swelling within said matrix upon absorption of water.

1. A method for producing a molded article selected from a container having a wall formed by forming a first mixture comprising a biodegradable polymer that forms a continuous matrix and has mixed therein particles of a hydrophilic material that is capable of swelling within said matrix upon absorption of water; forming a second mixture comprising a biodegradable polymer that forms a continuous matrix and has a reduced content of particles of a hydrophilic material that is capable of swelling within the matrix upon absorption of water; processing the first and second mixtures by injection molding to form a container wall comprising layers of the first and second mixtures in an overlapping arrangement and formed by the first layer and the second layer; A method comprising:

29. 30. The method of claim 28, comprising processing the first and second mixtures to form a multi-layer "sandwich" type wall structure.

30. 30. The method according to claim 28 or 29, wherein the injection moulding is carried out by multi-component injection moulding or by overmolding.

31. 31. The method of any one of claims 28 to 30, wherein the second mixture contains less than 25% by weight, calculated on the total weight of the second mixture, of particles of a hydrophilic material capable of swelling within a matrix upon absorption of water.

32. 28. A container according to any of claims 1 to 27 for use as packaging and containers selected from bottles with sealing lids for various materials including water-based and oil-based products.

33. 33. The container of claim 32, wherein the container is used to store food, cosmetics and medicines.

34. 34. The container according to claim 32 or 33, wherein the container is used for storing or serving sugar-containing natural or cooked products selected from honey and jams, dry substances or dry natural or cooked or otherwise prepared ingredients selected from milk powders, dried fruits, soups, meat and fish, and spices and tea, cocoa and coffee.

Citation Information

Patent Citations

  • Pelletizing wood

    CA1171656A

  • Plant fiber composition, composite material, and preparation method and applications thereof

    CN101712804A

  • Extrusion molding device for large-size wood-plastic composite plate

    CN107932874A

  • Thermoplastic composite material reinforced with hemp fibers

    EP0319589A1

  • Biodegradable board and molded article

    JP1995119098A